Handbook of Energy Governance in Europe
145 illus., 115 illus. in color. eReference.
Keywords: This Handbook provides the most comprehensive account of energy governance in Europe, examining both energy governance at the European level and the development of energy policy in 30 European countries. Authored by leading scholars, the first part of the book offers a broad overview of the topics of energy research, including theories of energy transitions, strategies and norms of energy policy, governance instruments in the field, and challenges of energy governance. In the second part, it examines the internal and external dimensions of energy governance in the European Union. The third part presents in-depth country studies, which investigate national trajectories of energy policy, including an analysis of the policy instruments and coordination mechanisms for energy transitions. It closes with a comparative analysis of national energy governance. This book is a definitive resource for scholars in energy and climate research as well as decision makers in national governments and EU institutions.